2013
DOI: 10.1121/1.4813397
|View full text |Cite
|
Sign up to set email alerts
|

The influence of glottal cross-section shape on theoretical flow models

Abstract: Physical and mathematical phonation models commonly rely on a quasi-one-dimensional flow model. The assumption of quasi-one-dimensional flow through a glottis with fixed length is analyzed for different cross-section shapes: Circle, rectangle, ellipse, and circular segment. A simplified flow model is formulated which accounts for kinetic losses, viscosity, and cross-section shape. It is seen that the cross-section shape cannot be neglected since it alters boundary layer development and hence the viscous contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It was shown that varying the cross-section shape alters the pressure distribution within a glottal constriction significantly, 20% up to 100% when comparing to the quasione-dimensional flow solution. 23 This amounts to the same order of magnitude as well-studied flow events such as the position of flow separation. 14,15,24 Therefore, applying a flow model for which the viscous contribution depends on the cross-section shape potentially affects the outcome of physical or mathematical models of phonation such as the phonation onset pressure threshold Pon.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…It was shown that varying the cross-section shape alters the pressure distribution within a glottal constriction significantly, 20% up to 100% when comparing to the quasione-dimensional flow solution. 23 This amounts to the same order of magnitude as well-studied flow events such as the position of flow separation. 14,15,24 Therefore, applying a flow model for which the viscous contribution depends on the cross-section shape potentially affects the outcome of physical or mathematical models of phonation such as the phonation onset pressure threshold Pon.…”
Section: Introductionmentioning
confidence: 78%
“…The pressure distribution Pðx; tÞ for x 0 x x s is obtained by integration of (1) 22,23 and results in a quadratic equation of volume flow rate U as follows:…”
Section: Phonation Onset Modelingmentioning
confidence: 99%
See 1 more Smart Citation